2013
DOI: 10.1123/ijspp.8.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Aerobic Power Characteristics of Male Professional Soccer Players, 1989–2012

Abstract: Purpose: The purpose of this investigation was to quantify maximal aerobic power (VO 2max ) in soccer as a function of performance level, position, age, and time of season. In addition, the authors examined the evolution of VO 2max among professional players over a 23-y period. Methods: 1545 male soccer players (22 ± 4 y, 76 ± 8 kg, 181 ± 6 cm) were tested for VO 2max at the Norwegian Olympic Training Center between 1989 and 2012. Results: No differences in VO 2max were observed among national-team players, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 18 publications
8
103
2
3
Order By: Relevance
“…This trend in physical performance could potentially be attributed to improvements in the players' physical capacity through enhanced physical preparation, or via an influx of players into the EPL with innately higher levels of physical fitness. Evidence would suggest VO2max of elite players has stayed relatively stable over the last two decades (Tønnessen, Hem, Leirstein, Haugen, & Seiler, 2013) although this may not be the most appropriate measure of physical capacity in elite team sports, with intermittent exercise capacity identified as a more sensitive measure than VO2max (Iaia, Rampinini, & Bangsbo, 2009;Krustrup & Bangsbo, 2001). Data from our laboratory indicates that the average distance covered by elite soccer players during the Yo-Yo Intermittent Endurance…”
Section: Discussionmentioning
confidence: 92%
“…This trend in physical performance could potentially be attributed to improvements in the players' physical capacity through enhanced physical preparation, or via an influx of players into the EPL with innately higher levels of physical fitness. Evidence would suggest VO2max of elite players has stayed relatively stable over the last two decades (Tønnessen, Hem, Leirstein, Haugen, & Seiler, 2013) although this may not be the most appropriate measure of physical capacity in elite team sports, with intermittent exercise capacity identified as a more sensitive measure than VO2max (Iaia, Rampinini, & Bangsbo, 2009;Krustrup & Bangsbo, 2001). Data from our laboratory indicates that the average distance covered by elite soccer players during the Yo-Yo Intermittent Endurance…”
Section: Discussionmentioning
confidence: 92%
“…Our results are very close to those found by some studies on soccer players in these two positions. 23,24 The greater running speed found at VT 2 in the players with higher aerobic performance appears to be a response that is related to the type of movement and the distance covered by these players (fullbacks and midfielders); these values are smaller in defenders and strikers; however, fullbacks and midfielders exhibit, much lower values than those observed in long-distance runners. This is probably due to the low emphasis given to specific aerobic training.…”
Section: ■ Discussionmentioning
confidence: 93%
“…These results are more strongly associated with the faster movements of the external defenders and wide midfielders [15,60]. Based on the great importance of this fast movement, some recent studies have suggested that elite football players have become faster over time, while their aerobic capacity has plateaued [22,58]. Additionally, the time-motion analysis carried out on elite football players revealed that the mean sprint duration mostly occurred in distances smaller than 20 m and within a time period of between 2 and 4 seconds [8,60].…”
Section: Discussionmentioning
confidence: 99%